A scale-inhibiting alloy material and its preparation method and application

By using scale-resistance alloy materials containing Cu, Ni, Sn, Zn, Pb and other components in the fluid pipeline, the dendrite structure is formed using the segregation tendency of Sn and Pb, the problems of dirt, corrosion and wax deposition in the fluid pipeline are solved, and efficient and long-term scale-resistance effect and environmentally friendly use are achieved.

CN118773477BActive Publication Date: 2025-04-22WUHAN YUANHAO AUTOMATION CONTROL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410763496.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-04-22
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The prior art has problems of energy waste, reduced production efficiency and safety hazards in preventing dirt, corrosion and wax deposition in fluid pipelines, and traditional methods are difficult to achieve fundamental water quality improvement and long-term use.

Method used

A scale-resistance alloy material is used, which contains components such as Cu, Ni, Sn, Zn, Pb, etc., and a thin dendrite metallographic structure is formed through the segregation tendency of Sn and Pb. The precipitation phases of Sn and Pb are enriched at the grain boundary to improve the strength, wear resistance and corrosion resistance of the alloy.

Benefits of technology

This alloy material can effectively resist corrosive media in the fluid, extend the service life of the scale resistor, reduce wax deposition, keep pipes unobstructed, significantly improve scale resistivity, and reduce pipe cleaning frequency and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118773477B_ABST
    Figure CN118773477B_ABST
Patent Text Reader

Abstract

The invention proposes a scale-inhibiting alloy material and a preparation method and application thereof, and relates to the technical field of alloy materials. The scale-inhibiting alloy material comprises the following components by weight percentage: Cu: 50%-70%; Ni: 11%-15%; Sn: 3%-6%; Zn: 5%-20%; Pb: 5%-10%; Fe: 0.1%-0.5%; Mn: 0.01%-0.3%; Cr: 0.003%-0.05%; Nb: 0.05%-0.2%; Si: 0.02%-0.1%; the metallographic structure of the scale-inhibiting alloy material is slender dendrites, and there are precipitation phases rich in Sn and Pb at the grain boundaries. Alloys with dendrite structure have high strength, wear resistance, corrosion resistance and wax resistance. When scale-inhibiting alloy materials are used for scale inhibition, they can transform calcium carbonate scale salt crystals into looser aragonite scale salts, which can be easily impacted by water flow and then carried away by the water flow. The scale inhibition effect is significant, and the scale inhibition rate is above 92%. The scale inhibitor can resist corrosive media and wax in the fluid, extending the service life of the scale inhibitor and the pipeline.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy materials, and in particular to a scale-inhibiting alloy material and a preparation method and application thereof. Background Art

[0002] Fouling and corrosion are common phenomena in fluid pipelines, which can cause many adverse consequences such as energy waste, reduced production efficiency, and equipment damage. The harm and losses brought to industrial production and civil fields are enormous. Countries around the world regard fouling and corrosion problems as important issues that need to be solved urgently.

[0003] Regarding the anti-scaling, anti-corrosion and anti-wax methods in fluid pipelines, the domestic market mostly adopts physical anti-scaling and descaling methods, such as mechanical descaling, magnetic field descaling, electrostatic descaling, activated carbon descaling, ion exchange resin descaling, ultrasonic descaling and other technical means. Commonly used anti-corrosion technologies include anti-corrosion materials, corrosion inhibitors, and cathodic protection. These traditional technologies not only consume huge amounts of energy and costs, but can only remove certain specific impurity ions in the water, and cannot fundamentally improve the water quality to achieve the purpose of descaling; and the use of chemical cleaning methods will cause the acid and alkali remaining in the water to pollute the water body, and corrode the equipment, causing safety hazards.

[0004] In recent years, chemical anti-scaling, descaling and anti-corrosion methods are gradually being replaced by new green and environmentally friendly anti-scaling and anti-corrosion technologies. The industry has also been conducting research for a long time to find new alloy materials with anti-scaling, anti-corrosion and anti-wax properties, so as to achieve new physical water treatment technologies that can not only remove scaling ions in water, but also save energy and reduce consumption, and be environmentally friendly. Summary of the invention

[0005] In view of this, the present invention proposes a scale-inhibiting alloy material and a preparation method and application thereof, which are used to achieve the purpose of preventing scale, corrosion and wax in fluid pipelines.

[0006] The technical solution of the present invention is achieved as follows: On the one hand, the present invention provides a scale-inhibiting alloy material, which includes the following components by weight percentage: Cu: 50% to 70%; Ni: 11% to 15%; Sn: 3% to 6%; Zn: 5% to 20%; Pb: 5% to 10%; Fe: 0.1% to 0.5%; Mn: 0.01% to 0.3%; Cr: 0.003% to 0.05%; Nb: 0.05% to 0.2%: Si: 0.02% to 0.1%; The metallographic structure of the scale-inhibiting alloy material is slender dendrites, and there are precipitation phases rich in Sn and Pb at the grain boundaries.

[0007] In the above alloy materials, it is mainly the two components Sn (tin) and Pb (lead) that cause the metallographic structure to be slender dendrites. This is because Sn and Pb have a strong tendency to segregate during the solidification process of the alloy, and will precipitate at the grain boundaries to form fine dendrite structures. This segregation phenomenon is due to the different solubility of Sn and Pb in solid and liquid metals, which leads to segregation during the solidification process. During the solidification of the alloy, the temperature and composition at the grain boundary are usually slightly different from those in the crystal, which will cause the solubility of Sn and Pb at the grain boundary to change. Since the solubility of Sn and Pb is higher at the grain boundary, they will preferentially precipitate from the solid crystal to form a fine dendrite structure.

[0008] Specifically, when the alloy solidifies, Sn and Pb will preferentially segregate from the liquid to the grain boundaries to form solid solutions and intermetallic compounds, and these precipitated phases will form fine dendrites at the grain boundaries. Due to the segregation effect of Sn and Pb, the grain boundaries will be rich in these two elements, that is, areas rich in Sn and Pb will be formed at the grain boundaries, thus forming a slender dendrite metallographic structure.

[0009] Alloys with dendrite structure have high strength, wear resistance and corrosion resistance, can effectively resist corrosive media in the fluid and extend the service life of the scale inhibitor. Alloys with dendrite structure have good wax resistance and can reduce the deposition and crystallization of wax inside the pipeline, preventing the pipeline from being blocked by wax, helping to keep the pipeline unobstructed and smooth, and avoiding pipeline failure and shutdown caused by wax blockage.

[0010] On the basis of the above technical scheme, preferably, the following components are included by weight percentage: Cu: 55% to 65%; Ni: 11% to 13%; Sn: 3% to 5%; Zn: 16% to 19%; Pb: 6% to 8%; Fe: 0.1% to 0.3%; Mn: 0.01% to 0.2%; Cr: 0.003% to 0.01%; Nb: 0.05% to 0.1%; Si: 0.03% to 0.05%.

[0011] On the other hand, the present invention also provides a method for preparing the above-mentioned anti-scaling alloy material, comprising the following steps:

[0012] S1, prepare raw materials according to the weight percentage of each component;

[0013] S2. Place 0.8-1.5 cm thick charcoal in the crucible of the heating furnace, evenly place half of the Cu material on the charcoal by weight, then evenly place all the Ni material and Fe material, evenly place the Si material and the remaining half of the Cu material on top, and then sprinkle the covering agent;

[0014] S3. Open the furnace and raise the temperature to 1300℃-1350℃. After ensuring that all the metals are melted, add deoxidizer for deoxidation, then add Zn, Pb, Sn, Cr, Nb metal blocks, and stir slowly until all the metals are melted;

[0015] S4. Add Mn metal blocks for degassing and slag removal, adjust the temperature to 1200℃-1250℃, cast the molten metal into shape, cool for 5min-15min, and after the metal surface solidifies, water cool to 20℃-25℃.

[0016] Based on the above technical solution, preferably, in step S2, the heating furnace is an induction furnace.

[0017] On the basis of the above technical solution, preferably, in step S2, the Cu material includes electrolytic copper, and the copper content of the electrolytic copper is greater than 99.95%.

[0018] On the basis of the above technical solution, preferably, in step S2, the covering agent is graphite flakes or charcoal, and the added amount of the covering agent is 0.8% to 1.6% of the weight of the Cu material.

[0019] On the basis of the above technical solution, preferably, in step S3, the deoxidizer comprises a phosphor-copper alloy, and the phosphorus in the phosphor-copper alloy accounts for 0.05% to 0.5% of the weight of the copper liquid.

[0020] Phosphor copper alloy deoxidation refers to the removal of oxygen in the alloy by adding an appropriate amount of phosphorus during the alloy preparation process. The specific mechanism of phosphor copper alloy deoxidation is as follows: Reaction of phosphorus and oxygen: Phosphorus reacts with oxygen at high temperature to form phosphorus oxides. These phosphorus oxides will float on the surface in the alloy melt and be removed, thereby reducing the oxygen content in the alloy; Phosphorus reducibility: Phosphorus has a strong reducibility and can undergo a reduction reaction with oxygen to reduce oxygen to oxides, and then convert them into phosphorus oxides. In this way, the oxygen element is effectively removed; Phosphorus oxygen absorption: Phosphorus has a strong oxygen absorption in the alloy melt, can absorb oxygen and form oxides, and then be excluded from the melt. This can effectively reduce the oxygen content in the alloy. In general, phosphorus copper alloy deoxidation mainly removes oxygen from the alloy through the chemical reaction, reduction reaction and oxygen absorption of phosphorus and oxygen, thereby improving the purity and performance of the alloy.

[0021] On the basis of the above technical solution, preferably, in step S4, the degassing of the Mn metal block is carried out within the first 3 minutes of casting.

[0022] The purpose of adding Mn metal blocks for degassing is to remove the gas in the alloy within the first 3 minutes of casting. Mn metal can undergo redox reaction with oxygen in the alloy at high temperature to generate oxides and release oxygen. This helps to remove oxygen from the alloy and reduce the gas content; Mn metal has strong gas absorption properties and can absorb gases in the alloy, such as hydrogen and oxygen, thereby reducing the gas content in the alloy; Mn metal can diffuse in the alloy and penetrate into bubbles, causing the bubbles to burst and release gas, thereby reducing the gas content in the alloy; this step is performed within the first 3 minutes of casting to remove the gas as quickly as possible to ensure the quality of the alloy.

[0023] The present invention provides an application of the above-mentioned anti-scaling alloy material. The anti-scaling alloy material is prepared by the above-mentioned method for preparing the anti-scaling alloy material and is used for preparing an anti-scaling, anti-corrosion and anti-wax anti-scaling device in a fluid pipeline.

[0024] On the basis of the above technical solution, preferably, the scale inhibitor comprises at least 6 pieces of scale-inhibiting alloy material, each piece of scale-inhibiting alloy material has a thickness of 5 to 10 mm, and the distance between adjacent scale-inhibiting alloy materials is 3 to 5 cm.

[0025] Increasing the amount of anti-scaling alloy material can increase the surface area of ​​the pipe that contacts the anti-scaling material, thereby improving the anti-scaling effect. When the amount of anti-scaling material is large enough, it can cover the inner surface of the pipe more comprehensively, effectively preventing the adhesion of scale, corrosion products and wax. However, too much anti-scaling material may increase manufacturing costs and installation difficulties, so a trade-off needs to be made between anti-scaling effect and cost.

[0026] If the spacing is too large, there will be holes and gaps inside the pipeline, which are easy to be invaded by dirt; if the spacing is too small, it may cause competition and interference between scale inhibition materials, affecting the scale inhibition effect. Therefore, it is necessary to determine the optimal spacing between adjacent scale inhibition alloy materials.

[0027] The scale-inhibiting alloy material of the present invention has the following scale-inhibiting mechanism: when circulating water passes through, if the scale-inhibiting alloy material is not used, calcium ions in the water body react with carbonate ions to generate calcium carbonate precipitation, thereby causing scaling. When the scale-inhibiting alloy material is used, zinc in the surface alloy of the scale-inhibiting alloy material is easily dissolved and precipitated to cause dezincification. Zinc ions are dissolved in the aqueous solution, compete with calcium ions in the water body, and form zinc carbonate precipitation with carbonate ions. Each crystal face of the zinc carbonate crystal has different selectivity for the adsorption of zinc ions, and the presence of zinc ions on the surface of the crystal changes the growth rate of each crystal face, affects the formation of carbonate nuclei and the crystal orientation, and causes the crystal structure to change. The crystal structure changes from a thermodynamically stable form to a thermodynamically unstable form, and the scale salt crystal becomes a loose aragonite-type scale salt. The adhesion between particles becomes smaller, and in the presence of water flow, it is easy to be impacted into small particles and then carried away by the water flow, and is not deposited in the pipeline, thereby playing a scale-inhibiting role.

[0028] The scale-inhibiting alloy material of the present invention and its preparation method and application have the following beneficial effects compared with the prior art:

[0029] (1) The present invention optimizes the formula and designs the preparation method reasonably. Due to the different solubilities of Sn and Pb in solid and liquid metals, segregation occurs during the solidification process. The metallographic structure of the prepared anti-scaling alloy material is slender dendrites, and there are precipitation phases rich in Sn and Pb at the grain boundaries. Sn and Pb have a strong tendency to segregate during the solidification of the alloy, and will precipitate at the grain boundaries to form a fine dendrite structure. The alloy with the dendrite structure has high strength, wear resistance and corrosion resistance, can effectively resist the corrosive medium in the fluid, and extend the service life of the anti-scaling device. The alloy with the dendrite structure has good wax resistance, can reduce the deposition and crystallization of wax inside the pipeline, prevent the pipeline from being blocked by wax, help keep the pipeline unobstructed and smooth, and avoid pipeline failure and shutdown caused by wax blockage;

[0030] (2) The scale inhibitor is prepared by using the scale-inhibiting alloy material. When used for scale inhibition, cations mainly composed of zinc ions are precipitated by the tiny primary battery reaction of the copper-zinc alloy and form zinc carbonate precipitation with carbonate ions, which affects the nucleation and growth of calcium carbonate crystals, causing the crystal structure to change. The scale salt crystals change from the thermodynamically stable calcite form to the metastable aragonite form. The aragonite scale salt is looser, the adhesion between the particles becomes smaller, and the bonding force with the pipe wall is reduced. In the presence of water flow, it is easy to be impacted into small particles and then carried away by the water flow, thereby playing a role in scale inhibition. The scale inhibition effect is significant, and the scale inhibition rate is above 92%;

[0031] (3) Rationally design the number of anti-scaling alloy materials in the scale inhibitor and optimize the spacing between adjacent anti-scaling alloy materials, thereby enhancing the anti-scaling effect of the anti-scaling alloy materials and optimizing the anti-scaling effect of the scale inhibitor, which is beneficial to reducing the cleaning frequency and maintenance cost of the pipeline, extending the service life of the pipeline, and improving the reliability and safety of the pipeline. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 Schematic diagram of the scale inhibition mechanism of the scale inhibition alloy material of the present invention;

[0034] Figure 2 This is the metallographic structure diagram of the scale-inhibiting alloy material of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] The present embodiment provides an anti-scaling alloy material, which includes the following components by weight percentage: Cu: 63%; Ni: 13%; Sn: 4.5%; Zn: 13%; Pb: 6%; Fe: 0.2%; Mn: 0.1%; Cr: 0.05%; Nb: 0.1%; Si: 0.05%; the metallographic structure of the anti-scaling alloy material is slender dendrites, and there are precipitation phases rich in Sn and Pb at the grain boundaries.

[0038] This embodiment provides a method for preparing a scale-inhibiting alloy material, comprising the following steps:

[0039] S1, prepare raw materials according to the weight percentage of each component;

[0040] S2. Place 1 cm thick charcoal in the crucible of the induction furnace, evenly place half of the Cu material (electrolytic copper) on the charcoal by weight, then evenly place all the Ni material and Fe material, evenly place the Si material and the remaining half of the Cu material on top, and then sprinkle the charcoal covering agent. The amount of the charcoal covering agent added is 1% of the weight of the total Cu material.

[0041] S3. Open the furnace and raise the temperature to 1300°C. After ensuring that all the metals are melted, add phosphor copper alloy for deoxidation. The phosphorus in the phosphor copper alloy accounts for 0.3% of the weight of the copper liquid. Then add Zn, Pb, Sn, Cr, and Nb metal blocks and stir slowly until all the metals are melted.

[0042] S4. 3 minutes before casting, add Mn metal blocks for degassing and slag removal, adjust the temperature to 1200℃, cast the molten metal, cool for 10 minutes, and after the metal surface solidifies, water cool to 25℃.

[0043] This embodiment provides an application of a scale-inhibiting alloy material for preparing a scale inhibitor for preventing scale, corrosion and wax in a fluid pipeline. The scale inhibitor includes 6 pieces of scale-inhibiting alloy material with a thickness of 8 mm, and the distance between adjacent scale-inhibiting alloy materials is 4 cm.

[0044] Example 2

[0045] The present embodiment provides an anti-scaling alloy material, which includes the following components by weight percentage: Cu: 50%; Ni: 15%; Sn: 4.5%; Zn: 20%; Pb: 10%; Fe: 0.2%; Mn: 0.1%; Cr: 0.05%; Nb: 0.1%; Si: 0.05%; the metallographic structure of the anti-scaling alloy material is slender dendrites, and there are precipitation phases rich in Sn and Pb at the grain boundaries.

[0046] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0047] This embodiment provides an application of a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0048] Example 3

[0049] The present embodiment provides an anti-scaling alloy material, which includes the following components by weight percentage: Cu: 70%; Ni: 11%; Sn: 3.5%; Zn; 5%; Pb: 10%; Fe: 0.2%; Mn: 0.1%; Cr: 0.05%; Nb: 0.1%; Si: 0.05%; the metallographic structure of the anti-scaling alloy material is slender dendrites, and there are precipitation phases rich in Sn and Pb at the grain boundaries.

[0050] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0051] This embodiment provides an application of a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0052] Example 4

[0053] The present embodiment provides an anti-scaling alloy material, which includes the following components by weight percentage: Cu: 58%; Ni: 15%; Sn: 6%; Zn; 10.5%; Pb: 10%; Fe: 0.2%; Mn: 0.1%; Cr: 0.05%; Nb: 0.1%; Si: 0.05%; the metallographic structure of the anti-scaling alloy material is slender dendrites, and there are precipitation phases rich in Sn and Pb at the grain boundaries.

[0054] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0055] This embodiment provides an application of a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0056] Example 5

[0057] The present embodiment provides an anti-scaling alloy material, which includes the following components by weight percentage: Cu: 66%; Ni: 11%; Sn: 3%; Zn; 13%; Pb: 6.5%; Fe: 0.2%; Mn: 0.1%; Cr: 0.05%; Nb: 0.1%; Si: 0.05%; the metallographic structure of the anti-scaling alloy material is slender dendrites, and there are precipitation phases rich in Sn and Pb at the grain boundaries.

[0058] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0059] This embodiment provides an application of a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0060] Example 6

[0061] This embodiment provides a scale-inhibiting alloy material, which is the same as that of embodiment 1.

[0062] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0063] This embodiment provides an application of a scale-inhibiting alloy material for preparing a scale inhibitor for preventing scale, corrosion and wax in a fluid pipeline. The scale inhibitor includes 6 pieces of scale-inhibiting alloy material with a thickness of 8 mm, and the distance between adjacent scale-inhibiting alloy materials is 2 cm.

[0064] Example 7

[0065] This embodiment provides a scale-inhibiting alloy material, which is the same as that of embodiment 1.

[0066] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0067] This embodiment provides an application of a scale-inhibiting alloy material for preparing a scale inhibitor for preventing scale, corrosion and wax in a fluid pipeline. The scale inhibitor includes 6 pieces of scale-inhibiting alloy material with a thickness of 8 mm, and the distance between adjacent scale-inhibiting alloy materials is 3 cm.

[0068] Example 8

[0069] This embodiment provides a scale-inhibiting alloy material, which is the same as that of embodiment 1.

[0070] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0071] This embodiment provides an application of a scale-inhibiting alloy material for preparing a scale inhibitor for preventing scale, corrosion and wax in a fluid pipeline. The scale inhibitor includes 6 pieces of scale-inhibiting alloy material with a thickness of 8 mm, and the distance between adjacent scale-inhibiting alloy materials is 5 cm.

[0072] Example 9

[0073] This embodiment provides a scale-inhibiting alloy material, which is the same as that of embodiment 1.

[0074] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0075] This embodiment provides an application of a scale-inhibiting alloy material for preparing a scale inhibitor for preventing scale, corrosion and wax in a fluid pipeline. The scale inhibitor includes 6 pieces of scale-inhibiting alloy material with a thickness of 8 mm, and the distance between adjacent scale-inhibiting alloy materials is 6 cm.

[0076] Example 10

[0077] This embodiment provides a scale-inhibiting alloy material, which is the same as that of embodiment 1.

[0078] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0079] This embodiment provides an application of a scale-inhibiting alloy material for preparing a scale inhibitor for preventing scale, corrosion and wax in a fluid pipeline. The scale inhibitor includes 4 pieces of scale-inhibiting alloy material with a thickness of 8 mm, and the distance between adjacent scale-inhibiting alloy materials is 4 cm.

[0080] Embodiment 11

[0081] This embodiment provides a scale-inhibiting alloy material, which is the same as that of embodiment 1.

[0082] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0083] This embodiment provides an application of a scale-inhibiting alloy material for preparing a scale inhibitor for preventing scale, corrosion and wax in a fluid pipeline. The scale inhibitor includes 5 pieces of scale-inhibiting alloy material with a thickness of 8 mm, and the distance between adjacent scale-inhibiting alloy materials is 4 cm.

[0084] Example 12

[0085] This embodiment provides a scale-inhibiting alloy material, which is the same as that of embodiment 1.

[0086] This embodiment provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Embodiment 1.

[0087] This embodiment provides an application of a scale-inhibiting alloy material for preparing a scale inhibitor for preventing scale, corrosion and wax in a fluid pipeline. The scale inhibitor includes 7 pieces of scale-inhibiting alloy material with a thickness of 8 mm, and the distance between adjacent scale-inhibiting alloy materials is 4 cm.

[0088] Comparative Example 1

[0089] This comparative example provides an anti-scaling alloy material, which includes the following components by weight percentage: Cu: 63%; Ni: 13%; Sn: 4.5%; Zn: 19%; Fe: 0.2%; Mn: 0.1%; Cr: 0.05%; Nb: 0.1%; Si: 0.05%; the metallographic structure of the anti-scaling alloy material is slender dendrites, and there are Sn-rich precipitation phases at the grain boundaries.

[0090] This comparative example provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Example 1.

[0091] This comparative example provides an application of a scale-inhibiting alloy material, which is the same as Example 1.

[0092] Comparative Example 2

[0093] This comparative example provides an anti-scaling alloy material, which includes the following components by weight percentage: Cu: 63%; Ni: 13%; Zn: 17.5%; Pb: 6%; Fe: 0.2%; Mn: 0.1%; Cr: 0.05%; Nb: 0.1%; Si: 0.05%; the metallographic structure of the anti-scaling alloy material is slender dendrites, and there are Pb-rich precipitation phases at the grain boundaries.

[0094] This comparative example provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Example 1.

[0095] This comparative example provides an application of a scale-inhibiting alloy material, which is the same as Example 1.

[0096] Comparative Example 3

[0097] This comparative example provides an anti-scaling alloy material, which includes the following components by weight percentage: Cu: 64.5%; Ni: 15%; Zn: 20%; Fe: 0.2%; Mn: 0.1%; Cr: 0.05%; Nb: 0.1%; Si: 0.05%.

[0098] This comparative example provides a method for preparing a scale-inhibiting alloy material, which is the same as that of Example 1.

[0099] This comparative example provides an application of a scale-inhibiting alloy material, which is the same as Example 1.

[0100] Evaluation of scale inhibition effect:

[0101] 1. The scale inhibitors prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were applied to the fluid pipeline, and the fluid pipeline without the scale inhibitor was used as the control group. A sheet of the same material as the fluid pipeline was selected and placed in the pipeline. The circulation treatment was carried out for 24 hours, and the weight difference before and after the sheet was measured as the mass of the scale. The scale mass of Examples 1 to 10 was recorded as M, and the scale mass of the control group was recorded as N. The scale inhibition rate was calculated as follows:

[0102]

[0103] The scale inhibition rates of Examples 1 to 10 are shown in Table 1.

[0104] 2. Referring to the standard "GB / T 10125-2021 Artificial atmosphere corrosion test salt spray test", the corrosion resistance of the scale-inhibiting alloy materials prepared in Examples 1 to 10 and Comparative Examples 1 to 3 was tested.

[0105] 3. Example 1 was applied to the boiler circulating cooling water system of non-ferrous metal smelting. An equipment scale inhibitor made of the anti-scaling, anti-corrosion and anti-wax alloy material prepared in Example 1 was installed at the water inlet end of the screw expander plate cooler to verify the anti-scaling and anti-corrosion effect of the alloy. The data are shown in Table 2.

[0106] Table 1

[0107]

[0108]

[0109] Table 2

[0110]

[0111] As shown in Table 1, the scale inhibition rates of Examples 1 to 5 are all above 92%, indicating that the scale inhibition alloy material prepared by the present application has an excellent scale inhibition effect; from the comparison between Example 1 and Examples 6 to 9, it can be seen that the spacing between adjacent scale inhibition alloy materials will affect the scale inhibition effect of the scale inhibitor, and a spacing that is too small or too large will reduce the scale inhibition rate, and the effect of a spacing that is too small is more obvious; from the comparison between Example 1 and Examples 10 to 12, it can be seen that the more pieces of scale inhibition alloy material, the higher the scale inhibition rate, and the better the scale inhibition effect of the scale inhibitor; from the comparison between Example 1 and Comparative Examples 1 to 3, it can be seen that the Sn and Pb elements alone The presence of Sn and Pb does not affect the metallographic structure, and the scale inhibition rate and corrosion resistance are slightly reduced. When both Sn and Pb elements do not exist, the scale inhibition rate does not drop much, but the corrosion resistance is significantly deteriorated. This is because Sn and Pb have a strong tendency to segregate during the solidification of the alloy. The presence of Sn and Pb elements alone can also precipitate at the grain boundaries to form fine dendrite structures. Alloys with dendrite structures have high strength, wear resistance and corrosion resistance, and can effectively resist corrosive media in the fluid. When both Sn and Pb elements do not exist, slender dendrite structures will not be formed at the grain boundaries, and the corrosion resistance is therefore reduced.

[0112] As shown in Table 1, after the scale inhibitor of the anti-scaling, anti-corrosion and anti-wax alloy material prepared in Example 1 was installed at the water inlet of the screw expander plate cooler, after 30 days of stable operation, both the pure water inlet and outlet water temperatures and the power machine bearing temperatures dropped significantly. After 75 days of stable operation, at the same speed of the screw expander, the pure water inlet temperature dropped from the highest 46°C to 33.6°C; the pure water outlet temperature dropped from the highest 53°C to 41°C; the bearing temperature dropped from the highest 62.5°C to below 55°C. The cooling effect of the plate cooler was significantly improved compared to before the alloy equipment was used, indicating that the equipment has a significant descaling effect, indicating that the scale-inhibiting alloy material provided in Example 1 of the present application has a good scale-inhibiting effect.

[0113] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A scale-inhibiting alloy material, characterized in that: The components include the following by weight percentage: Cu: 63%; Ni: 13%; Sn: 4.5%; Zn: 13%; Pb: 6%; Fe: 0.2%; Mn: 0.1%; Cr: 0.05%; Nb: 0.1%; Si: 0.05%; the metallographic structure of the anti-scaling alloy material is slender dendrites, and there are precipitated phases rich in Sn and Pb at the grain boundaries.

2. The method for preparing the scale-inhibiting alloy material according to claim 1, characterized in that: The following steps are involved: S1, prepare raw materials according to the weight percentage of each component; S2. Place 0.8-1.5 cm thick charcoal in the crucible of the heating furnace, evenly place half of the Cu material on the charcoal by weight, then evenly place all the Ni material and Fe material, evenly place the Si material and the remaining half of the Cu material on top, and then sprinkle the covering agent; S3. Open the furnace and raise the temperature to 1300℃-1350℃. After ensuring that all the metals are melted, add deoxidizer for deoxidation, then add Zn, Pb, Sn, Cr, Nb metal blocks, and stir slowly until all the metals are melted; S4. Add Mn metal blocks for degassing and slag removal, adjust the temperature to 1200℃~1250℃, cast the molten metal into shape, cool for 5min~15min, and after the metal surface solidifies, water cool to 20℃~25℃.

3. The method for preparing the scale-inhibiting alloy material according to claim 2, characterized in that: In step S2, the heating furnace is an induction furnace.

4. The method for preparing the scale-inhibiting alloy material according to claim 2, characterized in that: In step S2, the Cu material includes electrolytic copper, and the copper content of the electrolytic copper is greater than 99.95%.

5. The method for preparing the scale-inhibiting alloy material according to claim 2, characterized in that: In step S2, the covering agent is graphite flakes or charcoal, and the added amount of the covering agent is 0.8% to 1.6% of the weight of the Cu material.

6. The method for preparing the scale-inhibiting alloy material according to claim 2, characterized in that: In step S3, the deoxidizer includes phosphor-copper alloy, and the phosphorus in the phosphor-copper alloy accounts for 0.05% to 0.5% of the weight of the copper liquid.

7. The method for preparing the scale-inhibiting alloy material according to claim 2, characterized in that: In step S4, the degassing of the Mn metal block is carried out within the first 3 minutes of casting.

8. Application of a scale-inhibiting alloy material, characterized in that: The anti-scaling alloy material is prepared by the preparation method described in any one of claims 2 to 7, and is used to prepare anti-scaling, anti-corrosion and anti-wax anti-scaling devices in fluid pipelines.

9. The use of the scale-inhibiting alloy material according to claim 8, characterized in that: The scale inhibitor comprises at least 6 pieces of scale-inhibiting alloy materials, each piece of scale-inhibiting alloy material has a thickness of 5 to 10 mm, and the distance between adjacent scale-inhibiting alloy materials is 3 to 5 cm.

Citation Information

Patent Citations

  • Anti-wax anti-scaling anti-corrosion alloy material

    CN102094135A

  • Full intelligent horizontal type antiscaling device

    CN107385274A

  • Metastable microcrystalline structural alloy and preparation method thereof

    CN109252065A

  • Wear-resistant tin-lead bronze alloy material for engineering vehicle

    CN113322398A